A SEMIOTIC ANALYSIS OF POLITICAL CARTOON OF IRAN NUCLEAR PROGRAM - SAFALIA, FITRIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotic, political cartoon, sign, icon, symbol, index, connotation  In our society, information, ideas, or opinions can be delivered through news. The existence of news is very important in spreading information through the public since many events happen everyday and bring effects to the society. Nowadays, news is not only delivered through the words but also delivered through pictures and cartoons. In this study, the writer uses political cartoon as the object. The political cartoon was analyzed by using Semiotics study. There are five political cartoons that were analyzed in this study. All of the political cartoons taken were have topic about Iran nuclear program. This study has two problems to be solved: (1) What are semiotic signs that can be found on the political cartoons of Iran nuclear program?, and (2) What are the connotations built in political cartoons of Iran nuclear program?. Based on those problems, the writer formulates the objective of this study as follows: (1) To find out the semiotics signs of political cartoons of Iran nuclear program, and (2) To identify the connotation built in political cartoons of Iran nuclear program.This study uses qualitative approach by document analysis because the study focuses on identifying sign, interpreting connotation build which found in political cartoon of Iran nuclear program. The writer collected the data by looking at the verbal and visual sign contained. This study applies typology of sign’s theory proposed by Pierce and also Barthes connotation theory.The study reveals that iconic signs are mostly used in these political cartoons. The writer found that there were 97 signs found in total consisting of 40 icons, 27 indexes and 30 symbols. The connotation can be made by relating all the sign employed in the political cartoons. The signs can also be related to the cultural value and social convention. Each sign has a very important role to build up expected additional idea of the political cartoons. It has function to make clear, support and strengthen up a message which the cartoonist tried to convey.The writer suggests that the next researchers conduct a study on semiotics by using another form of objects, for example poster, comic, advertisement, or movie poster. The next researchers are also suggested to use some other theories to gain better understanding about semiotics.